Soil-Transmitted Helminth infections reduction in Bhutan: A report of 29 years of deworming. - Tshering Dukpa; Nidup Dorji; Sangay Thinley; Wangchuk; Karma Tshering; Kinley Gyem; Diki Wangmo; Passang Lhamo Sherpa; Tshering Dorji; Antonio Montresor (PLoS ONE)
Soil Transmitted Helminth (STH) infections affect over 1.5 billion people worldwide. Although prevalent in all age groups, school aged children are a high-risk groups for STH infections. In Bhutan, epidemiological data on STH were collected from western Bhutan in 2003, which found a prevalence of 16.5%. However, little evidence is available on the prevalence of infection at national level. Therefore, this study was conducted with the aim to assess the prevalence and intensity of STH infections, and identify significant correlates of STH among students. A school-based survey was conducted in three regions of Bhutan. Two-stage cluster sampling was adopted to select a sample of 1500 students from 24 schools, in equal proportion from three regions of the country. A total of 1456 (97%) students were interviewed and their stool sample examined for the presence of parasites. Mini-FLOTAC technique was used to detect the parasite eggs/ova. The prevalence of any STH infection was 1.4%, with 0.8% Ascaris lumbricoides, 0.5% Trichuris trichiura and 0.2% hookworms. The eastern region had the highest prevalence at 2.3%. Except for one student who had moderate intensity of A. lumbricoides, the rest had light infection. Any STH presence was significantly associated with father's occupation, father's education level, type of house and the flooring of the house in which students reported to live. No significant associations were observed between water, sanitation and hygiene (WASH) variables measured and presence of any STH infection. The prevalence of STH was found to be very low with primarily light intensity in this study. Nonetheless, it was also found that the sanitation situation is not ideal in the country, with several students reporting constant or partial open defecation leading to environmental contamination. Based on this prevalence and in line with the WHO guideline, it is recommended that deworming be reduced to once a year in combination with concerted health education on proper hygiene and sanitation practice.